Diagnostik und Therapie bei HIV-Infektion – was muss der Hausarzt wissen? - Ankert, Juliane; Rößler, Steve; Flössner, Christian; Jablonka, Alexandra; Schleenvoigt, Benjamin T. (DMW - Deutsche Medizinische Wochenschrift, 2019)
According to the Robert Koch Institute, the estimated HIV prevalence in Germany is 86 100. On-third of the affected persons is over 50 years old. Overall, the prognosis of patients with HIV infection depends crucially on the time of diagnosis. The unfounded stigmatization of affected patients stands in the way of today's treatment options as it did 30 years ago. Every practice of primary care must also take into consideration the medical care of HIV-infected people. The purpose of this article is to make the general practitioner aware of this topic and to prepare for the necessary procedure in everyday practice in this rare but not unlikely situation.
Keywords: HIV; AIDS; Hausarzt; HIV-Test; Vorsorge